Komodifikasi Komunikasi Digital: Pemikiran Al-Khwarizmi dan Relevansinya - Sumanti, Elvi; Zulkarnain, Iskandar; Mailin, Mailin (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2025)
The digital era has transformed communication from a mere medium for exchanging information into an integral part of an algorithm-driven economic mechanism. Algorithms play a crucial role in managing the flow of information on digital platforms, making them strategic tools in digital capitalism. This study explores Al-Khwarizmi’s thoughts on algorithms and their relevance to the commodification of communication in the digital age. Using a qualitative approach based on literature review, this research analyzes how algorithms, initially developed for numerical systems, have evolved into instruments that regulate information dissemination in digital media. The findings reveal that algorithms function not only as filtering mechanisms but also as economic tools that direct content exposure based on the business interests of digital platforms. This study highlights the impact of algorithmic communication on information access, user privacy, and informational bias due to excessive personalization. Al-Khwarizmi’s perspective provides a valuable historical lens for understanding the shifting role of algorithms from mere computational systems to instruments of information control in the digital economy.